Akhuwat: Measuring Success for a Non-profit Organization. Issue 1 (March 2019) - Bashir, Mohsin; Saleem, Ashar; Ahmed, Ferhana
Dr Amjad Saqib, founder and CEO of Akhuwat —a non-profit interest-free microfinance organization—faced a dilemma in July 2014. He was worried if the organization was actually making an impact—the real impact—that he originally intended. The conventional measures being used to assess Akhuwat's performance, that is, financial performance, loan disbursement and recovery rates, had all shown impressive signs. For instance, the recovery rate had always been above 99 per cent since Akhuwat's inception. Still, Dr Saqib was concerned, as he wanted to know whether these measures had actually translated into achieving his original intention of founding Akhuwat, which was to increase tolerance, compassion, voluntarism and happiness, in the target communities. This concern was further aggravated in the backdrop of a rapid expansion plan that Akhuwat was following since 2010. Back in 2001, Dr Saqib founded Akhuwat in order to provide an alternative to conventional microfinance institutions, which he saw as exploitative and against the Islamic principles of mutual support, as these charged very high interest rates from poor borrowers. Akhuwat, on the other hand, charged zero interest on its microcredit products. It relied on charity and donations, instead of bank loans, as its lending base and for covering operational expenses. The organization underwent a rapid expansion after a credit injection from the provincial government in 2010, resulting in a sevenfold increase in its loan portfolio, which rocketed to PKR 2, 460 billion in 2014, and a fivefold increase in the number of branches, which stood at 289 across the country in 2014. This transition also brought many changes and challenges to the working style and performance monitoring of Akhuwat, which had traditionally operated in a rather informal manner. The case highlights Dr Saqib's worries regarding the effectiveness of these measures in achieving Akhuwat's intended impacts.